REKAYASA TEKNOLOGI ALAT PENGOLAHAN BIOETANOL DARI NIRA AREN - Lay, A. (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Engineering Design of Bioethanol Processing Machine from Palm NeeraThe research was conducted in Laboratory and engineering workshop of Indonesian Coconut and Palmae Research Institute, Manado from May to September 2009. The activities consisted of Bioethanol processing equipment, field testingof bioethanol product as machine fuel engine. Raw material characteristics (crude ethanol), material balance, physical conditions and processing system of unit processes and economically processing analysis were observed. Research result showed that use of bioethanol equipment could improved ethanol content of crude ethanol from 13-30% to 80-94% and from 83% to 95-97%. Mass balance varied and depended on characteristic of crude ethanol and heating process. Ethanol 97% could be used as machine engine with ratio of gasoline and ethanol 90:10. Use of bioethanol and gasoline blend can be used more efficient 12.5-29.0% than use of gasoline. Processing of crude ethanol 25-35% to produce ethanol 90-95% is profitable. The bioethanol equipment efficient to be used under farmer scale and medium industries scale.